If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(x + 7) + -1(x + -1)(x + 5) = 0 Reorder the terms: (-3 + x)(x + 7) + -1(x + -1)(x + 5) = 0 Reorder the terms: (-3 + x)(7 + x) + -1(x + -1)(x + 5) = 0 Multiply (-3 + x) * (7 + x) (-3(7 + x) + x(7 + x)) + -1(x + -1)(x + 5) = 0 ((7 * -3 + x * -3) + x(7 + x)) + -1(x + -1)(x + 5) = 0 ((-21 + -3x) + x(7 + x)) + -1(x + -1)(x + 5) = 0 (-21 + -3x + (7 * x + x * x)) + -1(x + -1)(x + 5) = 0 (-21 + -3x + (7x + x2)) + -1(x + -1)(x + 5) = 0 Combine like terms: -3x + 7x = 4x (-21 + 4x + x2) + -1(x + -1)(x + 5) = 0 Reorder the terms: -21 + 4x + x2 + -1(-1 + x)(x + 5) = 0 Reorder the terms: -21 + 4x + x2 + -1(-1 + x)(5 + x) = 0 Multiply (-1 + x) * (5 + x) -21 + 4x + x2 + -1(-1(5 + x) + x(5 + x)) = 0 -21 + 4x + x2 + -1((5 * -1 + x * -1) + x(5 + x)) = 0 -21 + 4x + x2 + -1((-5 + -1x) + x(5 + x)) = 0 -21 + 4x + x2 + -1(-5 + -1x + (5 * x + x * x)) = 0 -21 + 4x + x2 + -1(-5 + -1x + (5x + x2)) = 0 Combine like terms: -1x + 5x = 4x -21 + 4x + x2 + -1(-5 + 4x + x2) = 0 -21 + 4x + x2 + (-5 * -1 + 4x * -1 + x2 * -1) = 0 -21 + 4x + x2 + (5 + -4x + -1x2) = 0 Reorder the terms: -21 + 5 + 4x + -4x + x2 + -1x2 = 0 Combine like terms: -21 + 5 = -16 -16 + 4x + -4x + x2 + -1x2 = 0 Combine like terms: 4x + -4x = 0 -16 + 0 + x2 + -1x2 = 0 -16 + x2 + -1x2 = 0 Combine like terms: x2 + -1x2 = 0 -16 + 0 = 0 -16 = 0 Solving -16 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 4x+8=9x+13 | | 3z+9.75-7z=-5.15 | | 3.92=1.19+.39x | | 7-x--1=30 | | 8*2y=9 | | 2t^2-20t-1=0 | | 8y-6y=4 | | 18x^2+3x-15=0 | | 23=8+5y | | 5(x^2-1)+24x=0 | | x+2*0=9 | | 19=24-5t | | 4-4c=0 | | 30x^2+25x-30=0 | | -16t^2+160t+8=0 | | 12x+12x=24x | | 5(x^2-1)+24=0 | | -66-9x=34-5x | | 16yz= | | .875a=43 | | x*2-x-2=28 | | 4x+y=6x+5y | | x^4+2x^3-x^2+2x+1=0 | | 6(c-2)=-18 | | x-32=6x+23 | | 4+3x=.25x-2 | | 0=-5+b | | 2x-4=2x+-2+3 | | y=375-50(15-1) | | -56+4x=10x+16 | | 4-3f=7 | | -12-92=183-x |